SRUDI LITERATUR:PERKEMBANGAN EKONOMI KREATIF UNTUK PENINGKATAN PEREKONOMIAN MASYARAKAT DAN PEMERINTAH DAERAH - Humaira, Silva; Nurliza Lubis (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2024)
This paper aims to see that the Development of the Creative Economy influences the Economy of the Community and Local Government. From several literature studies conducted, it can be stated that the development of the Creative Economy has a significant effect on improving the Economy of the Community and Local Government because the creative economy has an important role in the development of the community's economy supported by the era of globalization which makes the community and the government required to be more advanced in the use of technology. The development of the creative economy has a very effective impact on increasing income. regions from various sectors, be it Tourism, Culinary, Commodities, MSMEs, and various other economic sectors. The suggestions for the future for implementing the Creative Economy can affect economic growth in an area. In running the creative economy to be more efficient, it is hoped that business people, be it MSME players or other business people, understand well how the creative economy system is so that the results obtained are more effective and can provide the desired results. Business people are also expected to understand and operate technology well in accordance with their expertise and need so that there are no mistakes in managing a business based on the creative economy. Local governments are also expected to prioritize the creative economy because it has the potential to be very significant in improving the community's economy and regional income.